Identification of Gastrointestinal Nematoda on Kacang Goat (Capra aegagrus hircus) In Tiakur Moa District Southwest Maluku - Noach, Steffanie; Ludji, Sherli Melani; Sukariada, Putu Juli; Tae, Agustina Viktoria (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2025)
Gastrointestinal nematodes are one of the common groups of parasites in ruminants, especially goats. These parasites are also affected livestock productivity. This study aims to identify gastrointestinal nematode parasites and prevalence of infection to kambing kacang in Tiakur, Moa District, Southwest Maluku. The samples in this study are fecal collected from 50 kacang goats that are raised semi-intensively by two local farms in Tiakur. The examination of parasites eggs was performed using the direct native method and the test results were analyzed descriptively. The results of this study reveal the prevalence of 80% gastrointestinal parasite in farm 1 and 92% in farm 2. Parasite species that are infected kacang goats in two local farms in Tiakur are Haemonchus contortus, Trichuris sp., and Trichostrongylus sp. Lack of knowledge from the farmers about the implementation of biosecurity and maintenance management has a significant impact on gastrointestinal parasite infections in goats. This study also supports the local farmers to increase and improve the knowledge and increase deworming schedules to prevent the animal from parasites infections.